IMPROVING THE LEGAL, ECONOMIC, AND SOCIAL PROTECTION OF WOMEN IN UZBEKISTAN (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This scientific article provides a comprehensive analysis of institutional and legislative transformations aimed at improving the legal, economic, and social protection system for women in the Republic of Uzbekistan. The main object of the study is the strategic development programs of New Uzbekistan and the latest conceptual changes made to the national legislation. The article evaluates the strict norms included in the newly revised Constitution, Criminal Code, and Administrative Responsibility Codes, specifically the criminalization of domestic violence, liability established for sexual harassment, and the socio-creative effectiveness of the "Women's Notebook" system using scientific-deductive methods.